Legal Certainty Regarding the Legal Status of Riau Tabir Batik Based on Law Number 28 of 2014 on Copyright - Endang Suparta; Ismansyah; Runtung; Saidin (International Conference on Economic Business and Social Science, 2025)
Initially, the only known batik was hand-drawn batik. Along with the increasing use of batik, batik technology has also developed rapidly.Now, in addition to traditional batik making, there is also "modern" batik production, the result of which is called modern batik. Based on the use of the terms traditional and modern, batik cloth can be distinguished into. The method used in this research employs several cases of copyright infringement. The approach to analyze the existing issues by conducting an analysis of several regulations related to copyright. There is an issue regarding the Legal Certainty Related to the Legal Status of Batik Tabir Riau. Based on Law Number 28 of 2014 on Copyright. The research concluded that batik works receive legal protection because they possess artistic value, both in their motifs, images, and color compositions. Batik is one of the products based on traditional knowledge with characteristic features inherent to batik as a cultural product that aligns with traditional knowledge, requiring comprehensive legal protection.